2017
DOI: 10.1098/rsta.2016.0173
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-high performance fibre-reinforced concrete under impact: experimental analysis of the mechanical response in extreme conditions and modelling using the Pontiroli, Rouquand and Mazars model

Abstract: To evaluate the vulnerability of ultra-high performance fibre-reinforced concrete (UHPFRC) infrastructure to rigid projectile penetration, over the last few years CEA-Gramat has led an experimental and numerical research programme in collaboration with French universities. During the penetration process, concrete is subjected to extreme conditions of pressure and strain rate. Plasticity mechanisms as well as dynamic tensile and/or shear damage are activated during the tunnelling phase and the cratering of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 21 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…In case of hard impact, various empirical formulae were proposed to predict the ballistic limit or the penetration depth into concrete and RC targets. Among them, Berriaud et al [26] proposed a perforation limit formula, whose range of validity has been extended later [29], taking into account the missile nose shape influence. The effects of the projectile nose shape on the extent of local damage were also investigated experimentally in case of soft impact [30].…”
Section: Analytical Perforation Prediction In Case Of Soft Impactsmentioning
confidence: 99%
See 2 more Smart Citations
“…In case of hard impact, various empirical formulae were proposed to predict the ballistic limit or the penetration depth into concrete and RC targets. Among them, Berriaud et al [26] proposed a perforation limit formula, whose range of validity has been extended later [29], taking into account the missile nose shape influence. The effects of the projectile nose shape on the extent of local damage were also investigated experimentally in case of soft impact [30].…”
Section: Analytical Perforation Prediction In Case Of Soft Impactsmentioning
confidence: 99%
“…Berriaud's model [26] or derived ones are based upon the uniaxial compressive strength after 28 days. Baroth et al [4] and Zingg et al [34] have shown that latter parameter is a poor indicator of concrete compressive strength under high confinement.…”
Section: Analytical Perforation Prediction In Case Of Soft Impactsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PRM damage model is coupled to the plasticity model proposed by Krieg [61] and Swenson & Taylor [62]. In this theme issue, the PRM model is used to numerically simulate the penetration process of a rigid projectile striking an ultra-high-performance fibre reinforced concrete structure [23]. As an alternative, the lattice discrete particle model can be used to simulate the dynamic behaviour of concrete by postulating interaction laws of a system of discrete polyhedral cells belonging to coarse aggregate particles or to the cementitious matrix of the concrete [63].…”
Section: Modelling and Numerical Methods Dedicated To Brittle Materialsmentioning
confidence: 99%
“…10 3 -10 6 s −1 according to LaLone & Gupta [41] and Zinszner [42]). More recently, this testing facility was used to investigate the tensile strength of an alumina ceramic [13], two SiC ceramics [14] ( figure 3a) and an ultra-high-performance concrete [23].…”
Section: Experimental Techniques Devoted To Brittle Materialsmentioning
confidence: 99%